1999
DOI: 10.1007/s002210050683
|View full text |Cite
|
Sign up to set email alerts
|

The supplementary motor area in motor and sensory timing: evidence from slow brain potential changes

Abstract: The present study investigated the processing of durations on the order of seconds with slow cortical potential changes. The question is whether trial-to-trial fluctuations in temporal productions or judgments correspond to variations in the amplitude of surface Laplacians computed over particular scalp regions. Topographical analyses were done using the source derivation method. Subjects performed three successive tasks: (1) time production, in which they produced a 2.5-s interval separated by two brief trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
244
6
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(280 citation statements)
references
References 45 publications
28
244
6
2
Order By: Relevance
“…The putamen has been proposed as the source of the brain's timing signal, possibly as part of a medial-frontal-striatal loop (Macar et al, 1999;Coull et al, 2004). Alternatively, Ivry and Spencer (2004) have proposed that the role of the basal ganglia in timing is to set the threshold for releasing an action or making a decision; in timing tasks, that threshold may be a point in time.…”
Section: Functional Connectivity Resultsmentioning
confidence: 99%
“…The putamen has been proposed as the source of the brain's timing signal, possibly as part of a medial-frontal-striatal loop (Macar et al, 1999;Coull et al, 2004). Alternatively, Ivry and Spencer (2004) have proposed that the role of the basal ganglia in timing is to set the threshold for releasing an action or making a decision; in timing tasks, that threshold may be a point in time.…”
Section: Functional Connectivity Resultsmentioning
confidence: 99%
“…They observed that potential changes (CNVs) were clearly linked with the duration to be judged: Electrical activity returned to its normal level earlier when the comparison interval was shorter rather than when the comparison interval was longer (see also Pfeuty, Ragot, & Pouthas, 2008). Macar, Vidal, and Casini (1999) reported quite similar results with a standard interval lasting 2.5 sec. Although the interval to be judged always lasted 2.5 sec, the CNV amplitude was larger when the interval was judged as being longer (see Figure 5).…”
Section: Cerebellummentioning
confidence: 90%
“…Our observation on the CNV-like negativity was consistent with ERP studies examining CNV elicited during time perception tasks. Macar et al (1999) reported that the CNV amplitude reflected the length of temporal estimates, and/or an index of time-based decision making and response (Macar & Vidal, 2009). As such, our results provide evidence that the CNV-like negativity is associated with error correction (correction of response timing) in our sensorimotor paradigm.…”
Section: Discussionmentioning
confidence: 99%